CoreALMlib: An ALM library translated from the Component Library. Issue 5 (14th October 2016) - INCLEZAN, DANIELA
Abstract: This paper presentsCore ALMlib, an ALM library of commonsense knowledge about dynamic domains. The library was obtained by translating part of theComponent Library (CLib ) into the modular action language ALM .CLib consists of general reusable and composable commonsense concepts, selected based on a thorough study of ontological and lexical resources. Our translation targetsCLib states (i.e., fluents ) and actions . The resulting ALM library contains the descriptions of 123 action classes grouped into 43 reusable modules that are organized into a hierarchy. It is made available online and of interest to researchers in the action language, answer-set programming, and natural language understanding communities. We believe that our translation has two main advantages over itsCLib counterpart: (i) it specifies axioms about actions in a more elaboration tolerant and readable way, and (ii) it can be seamlessly integrated with ASP reasoning algorithms (e.g., for planning and postdiction). In contrast, axioms are described inCLib using STRIPS-like operators, andCLib 's inference engine cannot handle planning nor postdiction.